Changing the E-Waste Management Paradigm: an Innovative Approach with the Electronic Waste-Atm System - Hakim, Luqman (SERUNAI, 2024)
Handling  electronic waste  (e-waste)  is one of the crucial environmental challenges in today's digital age. With the rapid growth of electronic device usage, the volume of e-waste generated continues to increase, posing significant risks to the environment and human health if not managed properly. One innovative solution that has emerged is the development of the "Electronic Waste-ATM" system. This system is designed to facilitate the collection, evaluation, and recycling of e-waste efficiently and safely. Electronic Waste-ATM utilizes advanced technology to automatically assess the physical condition and residual value of deposited electronics, while providing financial compensation to users instantly as an incentive to participate in the  program.  This research  evaluates the effectiveness of Electronic Waste-ATM in reducing the environmental impact of e-waste and provides  recommendations for  development and implementation. Through this analytical approach, this study provides valuable insights into the large-scale potential of the Electronic Waste-ATM system as part of a global solution to the e-waste management problem. The implementation of Electronic   Waste-ATM offers a number of advantages.    First, it increases the collection and rate of e-waste by directly rewarding users, which motivates more people to their old electronic devices.  Secondly, Electronic Waste-ATM helps reduce potentially polluting waste by ensuring that e-waste is processed at the right facilities. Thirdly, system supports environmental sustainability by reducing the need for new natural resources and curbing carbon emissions associated with the production of new electronic devices.